Nationality and the effect of statehood - األشخاذ امىصاعد امدكخِر ودىد جالل خصي (QALAAI ZANIST JOURNAL, 2018)
Nationality is the legal, political and spiritual relation between the individual and the state, and arranges mutual rights and obligations between them, deriving from the internal law, and the motivation of its existence is the necessary conditions for the formation, survival and continuity of the state. And by proving the belonging of the individual to the people of the state. Constituent nationality is the first nationality granted to citizens of the assets of the people of the State created by the succession of States because of independence and separation from the Predecessor State. Where the prominent importance of the study in the organization of the nationality of the establishment of the State of Kurdistan as a solution to the problematic right of the Kurdish people to self-determination as an impact of separation from the Iraqi state. Therefore, we will try to stop the compatibility of the legal provisions of the constitutive nationality upon the independence of states and their establishment as a picture of succession of countries, which the national legislator must deal with and organize in accordance with the interests of this country and its people, and taking into consideration the requirements of the international community. The State in accordance with the principles of human rights and international conventions, covenants and declarations in this regard, especially with regard to the nationality of natural persons.